Desenvolvimento, produtividade e composição bromatológica da primeira soqueira da cana-de-açúcar em função de fontes de fósforo - Pasuch, Bruno D'Orazio; Caione, Gustavo [UNESP]; Rodrigues, Marcos; Drescher, Alexander Hugo; Fernandes, Francisco Maximino (My University, 2012)
The aim of this study was to evaluate the development, yield and chemical composition of the first ratoon sugar cane, depending on the residual effect of phosphorus sources. The study was conducted in the municipality of Alta Floresta - MT. The experimental design was randomized blocks in factorial scheme 4x2, with four replications. The phosphorus sources were used: bone meal, Arad phosphate and triple superphosphate, and a control without the application of the nutrient. The varieties of sugar cane were planted IAC86-2480 and SP79-1011. We evaluated the plant height, stalk diameter, mass of a plant, number of stems, dry matter yield, P content of the plant and the chemical composition of the forage. The residual effect of fertilization, using different sources of phosphorus, no significant alterations in the development, yield and chemical composition of the first ratoon sugar cane, with little reduction in NDF and ADF when using the bone meal. The variety IAC86-2480 showed better results, providing a higher content of crude protein and phosphorus in the plant and increased production of dry mass.
Development, yield and chemical composition of the first ratoon sugar cane as a function of phosphorus sources
Keywords: Forage; Nutritive value; Phosphorus fertilization; Saccharum spp.